The Influence of Parent and Teacher Partnership, Guidance and Counseling Services, and Playing Stimulation Toward Social Skills in Early Childhood - Isti Rusdiyani*, Suryadi, Nopiana, Riswandi, Reza Rachmadtullah (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to determine the effect of collaboration between parents and teachers, the implementation of guidance and counseling, and the stimulation of games on the social skills of young children. This research was conducted at TK Negeri Pembina Tangerang Raya Region, with research samples of 29 teachers and 82 children. Variables consisting of parent collaboration with the teacher (X1), guidance and counseling services (X2), game stimulation (X3) and social skills (Y), were analyzed using path analysis to see the magnitude of the influence of each variable both partially and simultaneously. The results of the analysis show that: (1) the collaboration between parents and teachers has a significant direct effect on social skills of young children; (2) guidance and counseling services have a direct significant effect on social skills of early childhood; (3) game stimulation has a significant direct effect on social skills of early childhood; (4) the collaboration between parents and the teacher does not directly influence the stimulation of the game; (5) guidance and counseling services directly affect the stimulation of the game. Based on the results of these studies indicate that the role of parent collaboration with teachers, guidance and counseling services and stimulation of the game has a significant influence on the social skills of early childhood which is an important part of the life span of children.